Marginal zone lymphoma in elderly and geriatric patients. Issue 1 (March 2017) - Goede, Valentin
Abstract: Approximately 50% of patients with newly diagnosed marginal zone lymphoma (MZL) are of advanced age. For the three subtypes of MZL (extranodal MZL of mucosa-associated lymphoid tissue, splenic MZL, nodal MZL), the median age at diagnosis is around 65–70 years. Due to the lack of larger studies in MZL, little is known of the prevalence of comorbidity, polypharmacy, or geriatric syndromes in older patients with MZL. The impact of these concurrent conditions on the tolerability and feasibility of diagnostic or therapeutic procedures used in MZL has not been specifically investigated. However, some extrapolations can be made from other studies in cancer, thereby raising questions about potential benefits of geriatric assessment in older patients with MZL. Core of this article is a review of recommended diagnostic and therapeutic procedures in MZL in light of potential barriers and complications that might be encountered in elderly and geriatric patients with MZL.